THE IMPACT OF SETS-BASED SCIENCE LEARNING ASSISTED BY IT MEDIA ON SCIENCE LITERACY AND DIGITAL LITERACY - Setyo Eko Atmojo; Ari Kusuma Wardana (Jurnal Cakrawala Pendas, 2025)
This research aims to analyze the impact of SETS-based science learning assisted by IT-based media in increasing elementary school students' scientific literacy and digital literacy. This research method is an experimental nonequivalent control group design type. The subjects of this research were 50 grade V elementary school students divided into experimental classes and control classes. Data collection techniques in this research used observation sheets, questionnaires and test questions. The data analysis techniques used are descriptive percentages, difference tests (t-test) and increase tests (N-gain). The research results showed that the average mastery of scientific literacy aspects in the experimental class was 94.57% and in the control class it was 61.70%. Meanwhile, mastery of digital literacy aspects in the experimental class was 91.45% and in the control class it was 65.40%. Meanwhile, in the t test, the results of the post test obtained a value of t = 5.476 > t table = 1.998 and (p) count = 0 < 0.05, which means that there is a significant difference in learning achievement scores between the experimental group that used the product developed and the control group. . The results of the N gain test showed that the control group had an increase in the medium criteria (0.46) and the experimental group had an increase in the high criteria (0.74). Based on this, it can be concluded that SETS-based science learning assisted by IT-based media is effective and has a positive impact on elementary school students' mastery of scientific literacy and digital literacy.